PENGUKURAN PENINGKATAN PRODUKTIVITAS MENGGUNAKAN METODE OBJECTIVE MATRIX (OMAX) DENGAN PENDEKATAN ROOT CAUSE ANALYSIS (RCA) - Chriswahyudi Sutaman; Ekadipta; Babay Jutika Cahyana; Silvana Maharani (Institut Sains dan Teknologi Al-Kamal, 2026)
The increasing competition in the manufacturing industry requires companies to continuously enhance productivity in order to maintain efficiency and competitiveness. This study aims to measure the productivity level in the LED lamp production process using the Objective Matrix (OMAX) method combined with Analytic Hierarchy Process (AHP) weighting and Root Cause Analysis (RCA). The data analyzed include labor efficiency, machine utilization, product quality, setup time, and production costs during the period of January to December 2024. The OMAX calculation results indicate that the productivity index fluctuated throughout the research period, with an average value of 281. The highest index was achieved in July at 392, while the lowest occurred in October at 178. These fluctuations reveal instability in resource management and production performance. RCA, supported by the Fishbone Diagram and 5 Whys Analysis, identified the main root causes of decreased productivity: delayed preventive maintenance, inconsistent material quality, and uneven operator skills. Based on these findings, the study recommends implementing preventive maintenance scheduling, conducting regular operator training, and integrating a more comprehensive productivity monitoring system. These improvement efforts are expected to enhance process efficiency, reduce downtime, and ensure sustainable product quality. This research provides practical contributions as a reference for productivity evaluation and strategic decision-making in the manufacturing industry